UV, 광촉매 및 황산염 라디칼의 Multi-AOPs를 이용한 하수처리수 재이용 기술 - 박준영; 이상민; 진가현; Park, Junyoung; Lee, Sangmin; Jin, Gahyeon (KSCE Journal of Civil and Environmental Engineering Research, 2025)
As climate change intensifies, wastewater reuse technologies are emerging as crucial solutions for future water treatment challenges, particularly in addressing the urgent need for high-purity water in the semiconductor industry. This study investigated the application of multi-UV-based advanced oxidation processes (AOPs) that incorporate persulfate (PS) and titanium dioxide (TiO2) for treating effluent from wastewater treatment plants to meet semiconductor industry water quality standards. The treatment characteristics and efficiency of UV/PS and UV/TiO2/PS processes were systematically evaluated in lab-scale batch reactors, focusing on key operational parameters including UV light intensity, PS dosage, and TiO2 concentration. In the UV/PS process, optimal conditions of 26 W UV output and 3.7 mM (= 1 g/L) PS dosage achieved a maximum total organic carbon (TOC) removal efficiency of 89.08 % with a second-order rate constant of 1.98×10-2 L/mg·min. However, when UV treatment was applied independently, the TOC levels in treated water showed unstable patterns with an increasing trend. To address this limitation, the UV/TiO2/PS process was employed at 39 W UV output with 3.7 mM PS and 2 g/L TiO2, which resulted in an enhanced TOC removal efficiency of 92.58 % and a second-order rate constant of 2.18×10-2 L/mg·min. Although the overall removal efficiency was only marginally improved by the addition of TiO2, its inclusion significantly enhanced the stability of the AOPs process, ensuring consistent performance during long-term operation. These findings provide valuable insights for the development of industrial water reuse technologies by applying AOPs to effluent from wastewater treatment plants. 기후변화가 심화됨에 따라 하·폐수 재이용 기술이 미래 수처리의 핵심 해결방안으로 부상하고 있으며, 특히 반도체 산업에서 요구되는 고순도 용수 확보를 위한 기존 하폐수 처리공정의 고도화가 시급한 실정이다. 본 연구에서는 하수처리시설 방류수를 반도체 산업용 원수 수준으로 처리하기 위해 과황산염(PS)과 티타늄 다이옥사이드(TiO2)를 결합한 다중 자외선 기반 고도산화공정(multi-UV-based AOPs)을 적용하여 UV/PS 공정과 UV/TiO2/PS 공정의 처리 특성과 효율을 비교 평가하였으며, 실험실 규모의 회분식 반응기에서 UV 광원 세기, PS 주입량, TiO2 주입량 등 주요 운전인자들의 영향을 체계적으로 분석하였다. UV/PS 공정에서는 UV 출력 26 W와 PS 3.7 mM 최적 주입 조건에서 총 유기탄소(TOC) 제거율이 최대 89.08 %에 도달하였으며, 2차 속도상수는 1.98×10-2 L/mg·min을 나타냈다. 그러나 UV 단독처리를 적용하는 경우 처리수의 TOC가 안정되지 않고 상승하는 경향을 나타냈다. 이러한 한계를 개선하기 위해 적용한 UV/TiO2/PS 공정은 UV 출력 39 W, PS 3.7 mM, TiO2 2 g/L 조건에서 TOC 제거율이 최대 92.58 %까지 향상되었으며, 2차 속도상수는 2.18×10-2 L/mg·min을 기록하였다. TiO2의 주입으로 인하여 전체적인 제거 효율은 제한적으로 향상되었으나, AOPs 공정의 안정성을 크게 개선하여 장기 운전 시 안정된 적용성을 제공함을 확인할 수 있었다. 본 연구결과는 하수처리장 방류수의 고도처리를 통한 산업용수 재이용 기술 개발을 위한 실규모 적용 시 설계인자 도출에도 유용한 자료로 활용할 수 있을 것이다.